AuNP‐Modulated qPCR: An Optimized System for Detecting MIR Biophotons Released in DNA Replication. Issue 8 (2nd February 2023) - Yang, Yu; Peng, Daoling; Gu, Zhenglong; Jiang, Lei; Song, Bo
Abstract: Invited for the cover of this issue are Lei Jiang and Bo Song at the University of Shanghai for Science and Technology and the Technical Institute of Physics and Chemistry (CAS), and colleagues at Fudan University and South China Normal University. The image depicts how the hydrolysis of cellular energy molecules (i.e., ATP and dNTPs) releases mid‐infrared photons to efficiently drive biological processes including DNA replication. Read the full text of the article at 10.1002/chem.202203513 . Abstract : " ATP hydrolysis can release… MIR photons to efficiently drive intracellular reactions and processes including DNA replication ." This and more about the story behind the front cover can be found in the article at 10.1002/chem.202203513 ).